Mass spectrometry handbook - Lee, Mike S., 1960- (Hoboken, N.J. : J. Wiley & Sons, 2012)
Due to its enormous sensitivity and ease of use, mass spectrometry has grown into the analytical tool of choice in most industries and areas of research. This unique reference provides an extensive library of methods used in mass spectrometry, covering applications of mass spectrometry in fields as diverse as drug discovery, environmental science, forensic science, clinical analysis, polymers, oil composition, doping, cellular research, semiconductor, ceramics, metals and alloys, and homeland security. The book provides the reader with a protocol for the technique described (including sampling methods) and explains why to use a particular method and not others. Essential for MS specialists working in industrial, environmental, and clinical fields.
Includes bibliographical references and index.
Print version record.
Keywords: Mass spectrometry -- Handbooks, manuals, etc; Mass Spectrometry; SCIENCE -- Chemistry -- Analytic; Mass spectrometry; Massenspektrometrie; Handbooks; Electronic books; Handbooks and manuals